Degradação urbana decorrente da atividade de mineração para a construção civil em Teresina - PI - Sales, Matias Francisco Gomes de [UNESP] (2015)
The process of transformation of the space towards the production of infrastructures that promote social well-being, security and the right to housing are today, and probably always have been, the main cause of fairness by maintaining the natural balance of the environment. The mining activity, particularly, is characterized as one of the most severe forms of environmental degradation, because of the magnitude of the space to be explored, suppression of native vegetation characterization of the natural landscape, insertion of contaminants in the extraction process, among other evils. Apart from these directly related to the exploration process, there are those linked to the transport process, processing and marketing of raw materials mined. It soon becomes apparent that cities are born in environmentally impaired sites and remains in critical condition over time, as the urban ecosystem is always in the expansion process. Thus, the choice of the subject matter of this work is due to analysis of the problem of understanding existing between the quality of life and the constant mining activity in a degraded area. Directly search is an investigation about the socio-environmental conflicts associated with the use and urban degradation footprint resulting from mineral extraction activity that has the potential ability to achieve the communities to its surroundings. Thus, the spatial area for this research was the Vila Monte Verde, located in the Industrial City neighborhood located in the northern part of the city of Teresina, Piauí state capital. Justified the selection of this village, because the growing and intense material mineral extraction activity, used in construction and the proximity of these areas to residential communities as well As the present study seeks to prove that the environmental impact of the exploration process does not occur only the physical environment but also the social aspects, and how these transformations and...